1997
DOI: 10.1074/jbc.272.10.6311
|View full text |Cite
|
Sign up to set email alerts
|

Kit Receptor Dimerization Is Driven by Bivalent Binding of Stem Cell Factor

Abstract: Most growth factors and cytokines activate their receptors by inducing dimerization upon binding. We have studied binding of the dimeric cytokine stem cell factor (SCF) to the extracellular domain of its receptor Kit, which is a receptor tyrosine kinase similar to the receptors for platelet-derived growth factor and colonystimulating factor-1. Calorimetric studies show that one SCF dimer binds simultaneously to two molecules of the Kit extracellular domain. Ligand-induced receptor dimerization provides the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
98
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 30 publications
10
98
0
2
Order By: Relevance
“…It was shown that, given sufficiently strong feedback, (18,19) can generate patterns with a length scale of two cells (for a string) or three cells (for hexagons), in which cells with a high level of Delta expression (and low Notch) are surrounded by cells with low Delta (and high Notch) [4]. This is consistent with some fine-grained patterns observed in early development.…”
Section: Relation To the Model Of Collier Et Al [4]supporting
confidence: 71%
See 4 more Smart Citations
“…It was shown that, given sufficiently strong feedback, (18,19) can generate patterns with a length scale of two cells (for a string) or three cells (for hexagons), in which cells with a high level of Delta expression (and low Notch) are surrounded by cells with low Delta (and high Notch) [4]. This is consistent with some fine-grained patterns observed in early development.…”
Section: Relation To the Model Of Collier Et Al [4]supporting
confidence: 71%
“…This reduced model (21,22) and Collier et al's model (18,19) have the same homogeneous steady states (so that u = u), provided k i = 0 and…”
Section: Relation To the Model Of Collier Et Al [4]mentioning
confidence: 93%
See 3 more Smart Citations